Effects of Mechanical Loading on Intervertebral Disc Metabolism In Vivo - Iatridis, James C. (2006)
The overall goal of this work is to define more clearly which mechanical loading conditions are associated with accelerated disc degeneration. This article briefly reviews recent studies describing the effects of mechanical loading on the metabolism of intervertebral disc cells and defines hypothetical models that provide a framework for quantitative relationships between mechanical loading and disc-cell metabolism. Disc cells respond to mechanical loading in a manner that depends on loading magnitude, frequency, and duration. On the basis of the current data, four models have been proposed to describe the effects of continuous loading on cellular metabolism: (1) on/off response, in which messenger ribonucleic acid (mRNA) transcription remains altered for the duration of loading; (2) maintenance, characterized by an initial change in mRNA levels with return to baseline levels; (3) adaptation, in which mRNA transcription is altered and remains at a new steady state; and (4) no response. In addition, five hypothetical mechanisms that describe the long-term consequences of these metabolic changes on disc-remodeling are presented. The transient nature of gene expression along with enzyme activation/inhibition is associated with changes at the protein level. The hypothetical models presented provide a framework for obtaining quantitative relationships between mechanical loading, gene expression, and changes at the compositional level; however, additional factors, such as regulatory mechanisms, must also be considered when describing disc-remodeling. A more quantitative relationship between mechanical loading effects and the metabolic response of the disc will contribute to injury prevention, facilitate more effective rehabilitation treatments, and help realize the potential of biologic and tissue engineering approaches toward disc repair.